Effect of Cationic Groups on the Selectivity of Ternary Antimicrobial Polymers. Issue 21 (2nd August 2022) - Pham, Phuong; Oliver, Susan; Nguyen, Duong Thanh; Boyer, Cyrille
Abstract: Antimicrobial polymers (AMPs) have emerged as a promising approach to combat multidrug‐resistant pathogens. Developed from binary polymers, which contain cationic and hydrophobic groups, ternary polymers are enhanced by adding neutral hydrophilic monomers to improve their biocompatibility. Cationic groups have attracted significant attention owing to their pivotal role in AMPs. Although many studies have investigated the effect of cationic groups on antimicrobial activity of binary AMPs, there is a lack of comprehensive and systematic evaluation for ternary AMPs. Therefore, a library of 31 statistical amphiphilic ternary polymers containing different cationic groups, including primary amine, guanidine, and sulfonium groups is prepared to investigate the impact of cationic groups on antimicrobial activity and biocompatibility. It is shown that the cationic balance appears to be a critical factor influencing polymers' antibacterial activity and selectivity. The results reveal that the polymers that have the ratio of the cationic groups ranging between 50% and 60%, coupled with a cationic/hydrophobic ratio in the range of [1.4–2] and an appropriate neutral hydrophilic/hydrophobic balance, exhibited the highest selectivity toward mammalian cells. This study elucidates a structure–property‐performance relationship for ternary AMPs, which contributes to the development of AMPs capable of selectively targeting gram‐negative pathogens. Abstract : Antimicrobial polymers have emerged as a promising approach to combat multidrug‐resistant pathogens. A library of 31 amphiphilic ternary polymers containing different cationic groups, including primary amine, guanidine, and sulfonium groups, is prepared to investigate the impact of cationic groups on antimicrobial activity and cytotoxicity against mammalian cells.